Priorities of state policy in the direction of development of international cooperation in the aerospace industry - M.O. Psiuk (Економіка, управління та адміністрування, 2020)
Today, the aerospace industry is one of the leading science and capital-intensive industries in Ukraine. It is determined that the expansion of international cooperation, participation in global science and technology projects, maintaining competitiveness in the global space technology market remain the main directions of efforts by the relevant government agencies. It is mentioned that the importance of the space industry encourages national governments to pursue a separate policy to ensure its development. Institutional conditions play a special role in such a policy, including the priority of state policy in science, technology and education, in particular in the space sector, integration into the global innovation sphere, international cooperation and internationalization of research as the most important factor in the national space industry. The normative and legal support of Ukraine's international activity and cooperation with partner countries is analyzed. Ukraine’s cooperation with foreign countries in the field of space exploration and use is based on fundamental international agreements in this field, on Ukraine’s international obligations in the field of space activities and the current legislation of Ukraine regulating space activities. The paper substantiates the need to determine the main priorities of state support for the development of the domestic aerospace industry, which would contribute to the deepening and expansion of international cooperation programs and projects.